Historicizing Sunni Islam in the Ottoman Empire, c. 1450-c. 1750 - Krstić, Tijana (Islamic History and Civilization, 2021)
Articles collected in Historicizing Sunni Islam in the Ottoman Empire, c. 1450-c. 1750 engage with the idea that "Sunnism" itself has a history and trace how particular Islamic genres - ranging from prayer manuals, heresiographies, creeds, hadith and fatwa collections, legal and theological treatises, and historiography to mosques and Suﬁ convents - developed and were reinterpreted in the Ottoman Empire between c. 1450 and c. 1750. The volume epitomizes the growing scholarly interest in historicizing Islamic discourses and practices of the post-classical era, which has heretofore been styled as a period of decline, reﬂecting critically on the concepts of 'tradition', 'orthodoxy' and 'orthopraxy' as they were conceived and debated in the context of building and maintaining the longest-lasting Muslim-ruled empire. Readership: All interested in the debates on Sunni Islam and in the politics of religion and confessionalism in the early modern Ottoman Empire and in "post-classical" Islamic history more generally.